Strategi Guru dalam Mengatasi Perundungan di SMP Kristen Koha dengan Berbasis Pendidikan Agama Kristen - Tampilang, Risno; Talangamin, Sylvana; Palar, Yolanda Nany; Lomboris, Oklisya; Entile, Jelly; Markus, Wagey; Sangkoy, Riane V.; Janis, Dian Cassie; Tasiam, Asdella (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Bullying is a serious issue that affects the well-being and development of children in schools. The impact of bullying on students can have negative effects on their psychological and academic well-being, as well as affecting their social relationships and self-confidence. Researchers used a descriptive qualitative method. Researchers determined the sample, then data collection was carried out using interview techniques, observation, and document studies with the aim of obtaining comprehensive data. After that, the researchers analyzed the data by data reduction, presentation, and drawing conclusions. The results found that bullying occurs at Koha Christian Junior High School in various forms, especially verbal bullying. The impact of bullying on students includes psychological, academic, and social problems. Teachers have made various efforts to address bullying, including providing support and guidance to students, enforcing school rules, and working with parents. This research concludes that appropriate and planned strategies from the school, especially teachers, are crucial in addressing bullying issues in schools, and some concrete efforts that schools can make to address bullying include introducing and educating Christian values, collaborating with parents, enforcing school rules, emphasizing the reiteration of PERMENDIKBUD UU No. 82 of 2015, and establishing a complaint and monitoring center.